Gastric Bypass and Absorption of Antihypertensive Medications - Ahmed E. Altyar (Journal of King Abdulaziz University: Medical Sciences, 2018)
Little is known about the effects of gastric bypass on the absorption of prescription medications in the post-operative state. This poses a considerable clinical dilemma especially that the prevalence of morbid obesity continues to escalate in the United States of America, and as a result the number of gastric bypass procedures performed each year has similarly increased dramatically. The author presented a case of a 45-year-old male with refractory hypertension, secondary to mechanical complications after a Roux-en-Y gastric bypass procedure due to anatomical alteration contributing to pill retention and change in medications’ pharmacokinetics. Investigations for secondary causes of hypertension were made, patient’s blood pressure had become exceedingly difficult to control after his Roux-en-Y gastric bypass procedure and had only been controlled with IV medications. Further investigations confirmed the diagnosis of a mechanical gastrointestinal complication.